"A constant struggle to receive mental health care": health care professionals' acquired experience of barriers to mental health care services in Rwanda. Issue 1 (December 2015) - Rugema, Lawrence; Krantz, Gunilla; Mogren, Ingrid; Ntaganira, Joseph; Persson, Margareta
Abstract Background In Rwanda, many people are still mentally affected by the consequences of the genocide and yet mental health care facilities are scarce. While available literature explains the prevalence and consequences of mental disorders, there is lack of knowledge from low-income countries on health care seeking behavior due to common mental disorders. Therefore, this study sought to explore health care professionals' acquired experiences of barriers and facilitators that people with common mental disorders face when seeking mental health care services in Rwanda. Methods A qualitative approach was applied and data was collected from six focus group discussions (FGDs) conducted in October 2012, including a total of 43 health care professionals, men and women in different health professions. The FGDs were performed at health facilities at different care levels. Data was analyzed using manifest and latent content analysis. Results The emerging theme"A constant struggle to receive mental health care for mental disorders" embraced a number of barriers and few facilitators at individual, family, community and structural levels that people faced when seeking mental health care services. Identified barriers people needed to overcome were:Poverty and lack of family support, Fear of stigmatization, Poor community awareness of mental disorders, Societal beliefs in traditional healers and prayers, Scarce resources in mental health care andGender imbalance in care seeking behavior . The few facilitators to receive mental health care were:Collaboration between authorities and organizations in mental health and having aFamily with awareness of mental disorders and health insurance. Conclusion From a public health perspective, this study revealed important findings of the numerous barriers and the few facilitating factors available to people seeking health for mental disorders. Having a supportive family with awareness of mental disorders who also were equipped with a health insurance was perceived as vital for successful treatment. This study highlights the need of improving availability, accessibility, acceptability and quality of mental health care at all levels in order to improve mental health care among Rwandans affected by mental disorders.